2014
DOI: 10.1002/2013wr014151
|View full text |Cite
|
Sign up to set email alerts
|

Positive or negative correlation between actual and potential evaporation? Evaluating using a nonlinear complementary relationship model

Abstract: Understanding whether a positive or negative correlation between actual (E) and potential (E p ) evaporation is of great importance in detecting changes of E from E p . In this study, such correlation was evaluated via the linear regression slope (k) between E and E p derived from a nonlinear complementary relationship model. k varies with the relative degree of variability in the radiation term (E rad ) and aerodynamic term (E aero ) of E p , and is further affected by water availability. The sign of k is alw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 51 publications
2
45
0
Order By: Relevance
“…The increase in CR‐modeled ET a for most parts of western and northeastern China and the decrease for most parts of southern and eastern China are overall consistent with the results of a long‐term water‐balance analysis by Gao et al (), who concluded that ET a had a decreasing trend in most areas east of 100°E but showed an increasing trend in the western and the northern parts of northeastern China. Furthermore, Han, Tian, et al () also identified obvious decreasing trends in annual ET a over the past few decades for most stations in the humid regions while found the opposite for most stations in the arid regions. The decrease of ET a over the last three decades reported in the present study for the North China Plain is supported by the significant decline in topsoil water content during 1983–2012, which was due partially to the intensification of agricultural activities, as was demonstrated by Liu et al ().…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The increase in CR‐modeled ET a for most parts of western and northeastern China and the decrease for most parts of southern and eastern China are overall consistent with the results of a long‐term water‐balance analysis by Gao et al (), who concluded that ET a had a decreasing trend in most areas east of 100°E but showed an increasing trend in the western and the northern parts of northeastern China. Furthermore, Han, Tian, et al () also identified obvious decreasing trends in annual ET a over the past few decades for most stations in the humid regions while found the opposite for most stations in the arid regions. The decrease of ET a over the last three decades reported in the present study for the North China Plain is supported by the significant decline in topsoil water content during 1983–2012, which was due partially to the intensification of agricultural activities, as was demonstrated by Liu et al ().…”
Section: Discussionmentioning
confidence: 91%
“…The CR method has been widely used to estimate ET a at annual (Hobbins et al, ), monthly (Liu et al, ; Szilagyi & Jozsa, ; Szilagyi, ; Xu & Singh, ), weekly (Crago & Qualls, ), daily (Ma, Zhang, Szilagyi, et al, ; Ma, Zhang, Xu, et al, ; Ozdogan & Salvucci, ), and subdaily (Crago & Crowley, ; Han, Tian, et al, ) scales. However, Morton () suggested to avoid using the CR for periods shorter than 5 days over extended periods of time and/or over a large regional scale since large‐scale weather fronts may bring air masses over the land with a moisture signature decoupled from the underlying surface, which thus may temporarily disrupt the dynamic equilibrium of air humidity and surface fluxes in the land‐atmosphere system.…”
Section: Discussionmentioning
confidence: 99%
“…4) was carried out under the assumption that ∂P /∂E p = 0. Such an assumption is questionable given the well-known complementary relationship of evapotranspiration (Bouchet, 1963;Morton, 1983;Hobbins et al, 2001;Xu and Singh, 2005;Szilagyi and Jozsa, 2009;Han et al, 2014;Lintner et al, 2015), but also having in mind the important role of evapotranspiration in the recycling of precipitation (Shuttleworth, 1988;Elthair and Bras, 1994;Dominguez et al, 2006;Zemp et al, 2014). This paper presents a 3-D generalization of the Budyko hypothesis, intended to capture the mutual interdependence among E, E p , and P by involving the complementary relationship of evapotranspiration.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…A strong body of literature has been dedicated to study the relationship between E and E p , in particular the complementary relationship hypothesis (Bouchet, 1963;Morton, 1983;Hobbins et al, 2001;Xu and Singh, 2005;Szilagyi and Jozsa, 2009;Han et al, 2014). Before the study of Bouchet (1963) it was thought that a higher E p implied a greater E. He corrected this misconception based on energy balance arguments, demonstrating that as a surface dries up from initially wet conditions, E p increases while E decreases as the available water drops.…”
Section: The Complementary Relationship Of Evapotranspirationmentioning
confidence: 99%
“…The complementary principle reveals that the land surface wetness can be indirectly represented by the large‐scale advection of the drying power of air with a constant radiation energy input (Brutsaert, ). On the basis of this principle, Han et al (Han, Tian, & Hu, , Han, Hu, & Tian, ; Han, Hu, & Yang, ) extended the complementary relationship to a generalized form that expresses E / E Pen as a function of E rad / E Pen , shown as follows: EEPen=g()EradEPen. …”
Section: One‐sided Penman Approach and Complementary Principlementioning
confidence: 99%